Agroforestry land use: A way forward for reducing carbon footprint in agriculture - Prasad, Rajendra; Newaj, Ram; Chavan, S.B.; Dhyani, S.K. (Indian Journal of Agroforestry, 2020)
In modern era of environmental concern for global warming and climate change, all the activities relating to production of primary goods and services which harm environment by either disturbing its equilibrium or soiling it with pollutants and hazardous gasses are necessarily discouraged, and efforts are made to search for environment friendly processes and operations with low carbon footprint (i.e. low C emission and high C sink). Agriculture is the foundation of the national economies of many countries including India in spite of the fact that it is an important source of greenhouse gases and contribute toward global warming. This paper is an attempt to review how agriculture, with double characteristics of carbon sink as well as source, be used as mitigation/adaptation strategy against global warming by adopting modified methods and/or practices having low carbon inputs as well as low carbon outputs. Agroforestry land use being capable of producing various tangible and intangible benefits offers great potential of reducing carbon foot prints of agricultural production system. The additionality of agroforestry in the form of carbon sequestration, restoration of degraded land, ecosystem services etc over other mitigation options make it directly or indirectly low carbon production system. The paper also discusses some of the researchable and challenging issues such as assessment of area under agroforestry; estimation of above and below ground carbon, scaling up agroforestry adoption among small holders and strengthening of knowledge base to make agroforestry a win-win situation.